Intensification of methanol steam reforming process using Cu-modified Ni-based supported catalysts - González-Gil, Rafael; Herrera-Delgado, María Concepción; Larrubia-Vargas, María Ángeles; Alemany-Arrebola, Luis José; Pieta, I.S. (My University, 2019)
Hydrogen is conventionally manufactured in large scale by the steam reforming of methane or naphthas. The perspective of using hydrogen as a fuel depends of finding alternatives to the existing production technologies and feedstock. Oxygenated compounds are an interesting alternative and are been investigated extensively. The process of steam reforming of mixtures of oxygenated hydrocarbons does not contribute to a net increase in atmospheric CO2, as oxygenated obtained from renewable resources are considered to be CO2 neutral. In previous works has been demonstrate that Steam Reforming of oxygenated compounds is a complex reactions network where in a previous step, decomposition reaction take place followed by the reforming of decomposition products. Its known that DME (or methanol) receives particular attention due to its properties similar to those of liquefied petroleum gas (LPG)and it can be used as a clean high-efficiency compression ignition fuel. In other way, it has been demonstrate that DME-SR to produce H2 occurs through two main reactions in series, DME-Hydrolysis and MeOH-Steam Reforming. Therefore, bifunctional catalysts are necessary, with and acid funcion active in DME-HYD and a redox for reforming step. On the other hand, methanol is also regarded as an important feedstock for hydrogen production due to its high energy density and superior transportability, especially for small-scaled and portable fuel cell applications. In comparison with CH4-SR, the reaction temperature of methanol steam reforming is much lower and the gas off contains typically 60%-70% H2. In this contribution the Steam Reforming of MeOH has been studied using a Ni-based supported catalysts modified with copper and an optimized formulation was considered to incorporate in a microreformer, as an intensification of process to direct hydrogen supply on board.
Keywords: Hydrogen; Reforming; Oxygenated compounds; DME/MeOH-microreformer